The next moon. : The remarkable true story of a British agent behind the lines in wartime France. - HUE André; FOOT M.R.D.; SOUTHBY-TAILYOUR Ewen (Londres : Penguin Books, 2005)
Souvenirs d'un Héros de la résistance (de mère galloise).
Bibliogr. pp. 319-320
CCO
Bretagne
Ouvrage